Aliens in the Aegean – a sea under siege (ALAS) - Stelios Katsanevakis; Konstantinos Tsirintanis; Maria Sini; Vasilis Gerovasileiou; Nikoletta Koukourouvli (Research Ideas and Outcomes, 2020)
ALAS aims to fill knowledge gaps on the impacts of marine alien species in the Aegean Sea, and support marine managers and policy makers in prioritizing mitigation actions. The project will focus on under-studied alien-native interactions, priority and vulnerable habitats (such as shallow forests of canopy algae and underwater caves), and apply a multitude of approaches. It will apply a standardized, quantitative method for mapping Cumulative IMpacts of invasive Alien species on marine ecosystems (CIMPAL), according to which cumulative impact scores are estimated on the basis of the distributions of invasive species and ecosystems, and both the reported magnitude of ecological impacts and the strength of such evidence. Towards that direction, ALAS will improve our knowledge base and compile the needed information to estimate CIMPAL by (1) conducting a series of field experiments and surveys to investigate the impacts of selected invasive alien species on marine habitats, (2) producing high-resolution habitat maps in the coastal zone, refining the results of previous research efforts through fieldwork, remote sensing and satellite imaging, (3) producing species distribution models for all invasive species, based on extensive underwater surveys for the collection of new data and integrating all existing information. ALAS will incorporate skills and analyses in novel ways and provide high-resolution results at a large scale; couple classic and novel tools and follow a trans-disciplinary approach, combining knowledge from the fields of invasion biology, conservation biology, biogeography, fisheries science, marine ecology, remote sensing, statistical modelling; conduct for the first time in the Aegean Sea a comprehensive, high-resolution analysis of cumulative impacts of invasive alien species; and report results in formats appropriate for decision-makers and society, thus transferring research-based knowledge to inform and influence policy decisions.